The Digital Minbar: Repositioning Religious Authority and the Dynamics of Islamic Law in Contemporary Egypt's Virtual Landscape - Muhammad Latif Fauzi; Imam Mustofa; Ibnu Akbar Maliki; Faiz Husaini (MILRev: Metro Islamic Law Review, 2026)
The rapid development of digital technology has transformed the production, dissemination, and validation of religious knowledge, posing new challenges to traditional religious institutions in Egypt. This study examines how Al-Azhar and Dar al-Iftaʾ al-Miṣriyyah respond to the emergence of online religious actors who acquire authority through social media rather than through classical academic structures. This research is based on fieldwork and employs a descriptive qualitative design, drawing on sociological and religious-anthropological approaches. Primary data were obtained from leaders and scholars affiliated with Al-Azhar and Dar al-Iftaʾ al-Miṣriyyah, complemented by insights from socio-religious observers in Egypt who are members of the Special Branch of Nahdlatul Ulama (PCINU). Secondary data consist of fatwas and relevant scholarly literature. Data were collected through in-depth interviews and observation and analyzed using inductive qualitative techniques. The findings indicate that the digital space has democratized access to Islamic knowledge, enabling social media influencers, preachers, and informal online scholars to serve as alternative sources of fatwas and religious guidance for Egyptian Muslims. In response, Al-Azhar has prioritized strengthening its academically grounded digital presence, while Dar al-Iftaʾ has pursued a more dynamic strategy by expanding online fatwa services, launching social media campaigns, and developing multilingual outreach programs. At the same time, this study reveals that state regulation and political involvement in Egypt’s digital religious sphere significantly shape both the autonomy and public perception of official religious institutions. This article contributes to the broader discourse on Islamic authority by illustrating how classical institutions negotiate legitimacy amid algorithmic visibility, digital pluralism, and state control.